Atrial fibrillation is associated with worse short and long-term outcomes in critically ill patients. (3rd May 2023) - Paula, S; Oliveira, A; Silva, J; Santos, R; Simoes, A; Pereira, J G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF), either chronic or new onset, is common in critically ill patients. Its epidemiology and relationship with clinical outcomes, and the role of post-discharge anticoagulation, is unknown. Methods: Single-center retrospective, cohort study, evaluating all patients with AF admitted to a non-cardiac intensive care unit during a 54-month period. Their clinical outcomes at short-term (hospital discharge) and long-term (2-year follow-up) were evaluated. The hazard ratio (HR) with 95% CI for the 2-year all-cause mortality was computed for the whole population with AF compared with a matched one, without AF (1:2 ratio). Results: We screened 1357 patients, mean age 75±15.2 years, length of intensive care unit stay 4.7±5.1 days, hospital mortality 26%. We identified 215 (15.8%) patients with AF (66% chronic AF). The 2-year all-cause mortality was similar in patients with chronic or new onset AF (58.5% vs 50.7%, p=0.388). Only 85 patients received anticoagulation following their hospital discharge, mostly with chronic AF (74.5% vs 25.5%, p<0.001). We found no benefit from anticoagulation on the 2-year mortality rate (adjusted HR 1.09, 95% CI 0.63-1.86, p=0.6). We successfully matched 145 patients with AF with 290 controls. Mortality was higher in patients with AF, either in-hospital mortality or during long-term follow-up (mortality 53.8% vs 36.9%, HR 1.76; 95% CI 1.31-2.37, p=0.001). Conclusions: Patients with AF, both chronic and new onset, had significantly worse short- and long-term outcomes. No mortality benefit was found from anticoagulation after hospital discharge in patients with AF.